Oncological Safety, Surgical Outcome, and Patient Satisfaction of Oncoplastic Breast-Conserving Surgery With Contralateral Balancing Reduction Mammoplasty. Issue 4 (November 2021) - St Denis-Katz, Hannah; Ghaedi, Bahareh B.; Fitzpatrick, Aisling; Zhang, Jing
Introduction: Oncoplastic breast-conserving surgery (OBCS) is considered a cornerstone in the management of locally invasive breast cancer. We evaluated patient-reported outcomes of OBCS with contralateral balancing breast reduction mammoplasty and reviewed its oncologic outcomes and complications. Methods: This is mixed method study design using retrospective chart review and prospective cohort study. Patient demographics were reviewed. Outcome measures included clinicopathologic characteristics, complications, margin status, local recurrence, tumor histopathologies, duration of follow-up, patient satisfaction, self-esteem, event-related stress, and quality of life. Results: A total of 48 patients were included in this study. Complete excision with negative margins was obtained in 42 (87.5%) patients, positive margins in 6 (12.5%) patients, all who had re-excision with repeat lumpectomy. Thirteen patients developed minor complications, defined as being managed as an outpatient. No patients developed major complications requiring inpatient admission. These complications did not delay commencement of chemotherapy or radiotherapy. Postsurgery BREAST-Q TM26 scores demonstrated no statistical difference in satisfaction with breasts, nipples, and sexual well-being. There was high satisfaction with overall outcome with average score of 80.8%. For the Rosenberg self-esteem scale, the results were similar for 3- and 12-month post-operative indicating maintenance of normal self-esteem post-operatively. The Impact of Events Scale showed statistically significant difference at 12-month post-operative (25.1) when compared with preoperative scores indicating that patients had lower event-related stress. There was no significant change in Hospital Anxiety and Depression Scale. Conclusion: Our study has shown that the patient who undergo OBCS have high patient-reported outcomes with acceptable oncologic outcomes and complication rates.